Relationship of idiopathic femoral head necrosis with blood lipid metabolism and coagulation function: A propensity score-based analysis - Yu, Xiaolong; Zhang, Shengtao; Zhang, Bin; Dai, Min (Frontiers in Surgery, 2023)
Background: Nontraumatic osteonecrosis of the femoral head (ONFH) can be corticosteroid-induced, alcohol-induced, and idiopathic ONFH (IONFH). Although corticosteroid- and alcohol-induced ONFH has been investigated extensively regarding its relationship with blood lipids and coagulation factor levels. However, the effect of blood lipid metabolism and coagulation function on IONFH has rarely been studied. Therefore, this study aimed to analyse the relationship of IONFH with blood lipid and coagulation indicators. Methods: Total 680 patients diagnosed with IONFH in our institution during January 2011–June 2019 who met the inclusion criteria composed the case group; 613 healthy persons who underwent physical examination at our institution during the same period composed the control group. Propensity scores were used for baseline feature matching, and two matching groups each with 450 patients were established. After the matching, blood lipid and coagulation factor levels of both groups were comparatively analysed. Results: The case group showed significantly higher total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) levels, low-density/high-density lipoprotein (LDL/HDL) ratio, and apolipoprotein B (Apo-B) levels than the control group (p<0.05). Conversely, the HDL and apolipoprotein A (Apo-AI) levels in the case group were significantly lower than those in the control group (p<0.05). Regarding coagulation indicators, the activated partial thromboplastin time and prothrombin time were lower in the case group than in the control group; however, the differences were insignificant (p>0.05). Furthermore, fibrinogen (FIB) levels and thrombin time (TT) in the case group were higher than those in the control group. There were significant differences between the two groups only in terms of FIB levels (p<0.05), while TT was not significantly different (p>0.05). Conclusions: IONFH has strong associations with blood lipid metabolism and coagulation function, which provide an avenue for exploring the mechanism of IONFH.